PRESCHOOL DEVELOPMENT TRENDS IN UKRAINIAN SCHOOL PREPARATION SYSTEM OF EDUCATION AND UPBRINGING IN CANADA - Rusnak, Ivan; Vasylyk , Maryna (Mountain School of Ukrainian Carpaty, 2020)
The article has analyzed the main directions of evolution of Ukrainian preschool (preschool classes, preparatory classes) as a component of the system of national preschool education and upbringing of younger generations of Ukrainians in Canada during the second half of XX – the beginning of XXI century and an important factor that lays the foundations for the harmonious development of the child, promotes learning the native language, knowledge of history, culture, customs and traditions of his or her motherland. Relevance of the study is due to insufficient research of the outlined problem and expediency of using progressive ideas and experience of Canadian Ukrainians in national education of preschool children in educational space of Ukraine and modern ukrainian abroad. The purpose of the article is to identify the features of organization of the educational process in preschool classes, to clarify its role in personal development of the child and to prepare him or her for school. Achievement of the goal was promoted by use of the following research methods: general scientific (analysis, synthesis, systematization of the collected material), theoretical comprehension and generalization of the obtained results and their interpretation. It is established that preschool classes in the system of Ukrainian preschool education in Canada were organized in the early 50's of the twentieth century to prepare children for education in the system of native-language schooling and to continue national education and upbringing, the foundations of which were laid by children's rooms and kindergartens. They were situated in specially equipped premises that completely conformed to state requirements and worked according to curricula that provided, in addition to general development, national and religious upbringing of the child. Educational and material equipment of preschool classrooms and didactic support of educational process during the study period are constantly improved taking into account the achievements of preschool pedagogy and other fields of science, trends in the evolution of public preschool education in Canada, which ensures successful implementation of educational programs for preschool children and appropriate image in the environment of the Ukrainian diaspora.